Mengurai Kerangka Legislasi Sebagai Instrumen Perwujudan Hak Asasi Manusia - Utomo, Nurrahman Aji (Mahkamah Konstitusi Republik Indonesia, 2016)
This study seeks to examine the performance of legislation (lawmaking function) as the realization of human rights instruments. Scrutiny on the program period 2010-2014 national legislation, to determine the validity of the assuredness and values, human rights principles in the Law that were born in that period. The study was conducted by banging the process of formation of the Law, institutionalization are born by the state’s responsibility for human rights. The methods and approaches used in the study are in the type of normative or doctrinal study which aims to provide a systematic explanation of the rules, then analyzed the relationship between legislation and the realization of human rights as a state responsibility. Several approaches are used, among others, the statutory approach, the conceptual approach and the approach of the case. The relation between the lawmaking function with the realization of human rights, are in the state’s responsibility to look out of the politics of law. To parse each stage process that impact on the formal level, further analysis of the Law to include legal issues, regulatory patterns, models of responsibility of the state and its institutionalization. Proceeding from it, reflect on the process of legislation discover improper application of the limitation of the right, the context of government intervention and the application of the law. Collapsed it required for rights-based approach within the framework of law making function.